Bi-Plane Multicolor Scanning Illumination Microscopy with Multispot Excitation and a Distorted Diffraction Grating - Siwei Li; Yunke Zhang; Zhiwen Liao; Zengyuan Tian; Hairulazwan Hashim; Youjun Zeng; Yandong Zhang (Biosensors)
Multifocus microscopy has previously been demonstrated to provide volumetric information from a single shot. However, the practical application of this method is challenging due to its weak optical sectioning and limited spatial resolution. Here, we report on the combination of a distorted diffraction grating and multifocal scanning illumination microscopy to improve spatial resolution and contrast. DG is introduced in the emission path of the multifocal scanning illumination microscopy, which splits the fluorescence signal from different sample layers into different diffraction orders. After postprocessing, super-resolution wide-field images of different sample layers can be reconstructed from single 2D scanning.